Nutraceutical Value of Finger Millet [Eleusine coracana (L.) Gaertn.], and Their Improvement Using Omics Approaches - Kumar, Anil; Metwal, Mamta; Kaur, Sanveen; Gupta, Atul K.; Puranik, Swati; Singh, Sadhna; Singh, Manoj; Gupta, Supriya; Babu, B. K.; Sood, Salej; Yadav, Rattan (Frontiers in Plant Science, 2016)
The science of nutritional biology has progressed extensively over the last decade to develop food-based nutraceuticals as a form of highly personalized medicine or therapeutic agent. Finger millet (Eleusine coracana (L.) Gaertn.) is a crop with potentially tremendous but under-explored source of nutraceutical properties as compared to other regularly consumed cereals. In the era of growing divide and drawback of nutritional security, these characteristics must be harnessed to develop finger millet as a novel functional food. In addition, introgression of these traits into other staple crops can improve the well-being of the general population on a global scale. The objective of this review is to emphasize the importance of biofortification of finger millet in context of universal health and nutritional crisis. We have specifically highlighted the role that recent biotechnological advancements have to offer for enrichment of its nutritional value and how these developments can commission to the field of nutritional biology by opening new avenues for future research.